Anaplastic large cell lymphoma in a child presenting with cutaneous nodules and blisters - Cağlar, Kudret; Akyüz, Canan; Uner, Ayegül; Kutluk, Tezer; Yalçin, Bilgehan; Varan, Ali; Büyükpamukçu, Münevver (The Turkish Journal of Pediatrics, 2005)
A 13-year-old girl was admitted to our hospital with a one-month history of bullous skin lesions. Physical examination revealed ulcerated and nonulcerated cutaneous plaques, bullae, enlarged cervical and supraclavicular lymph nodes and hepatomegaly. In another hospital, histopathological diagnosis of a skin biopsy was reported to be consistent with tuberculosis and she was treated with antimycobacterial drugs. Since no response was obtained, she was referred to our center after a new lymph node biopsy was obtained. At our center, histopathological diagnosis was anaplastic lymphoma kinase (ALK)-negative anaplastic large cell lymphoma (ALCL). We started LMT chemotherapy regimen and initial response was complete. Eight months after initial admisision, she experienced cutaneous recurrence of disease while on maintenance protocol. Chemotherapy was changed to LSA4 regimen. She is still on chemotherapy and has been in complete remission for nine months. Clinicians should be aware of this uncommon presentation of ALCIL, which can be confused with other diseases clinically or histologically.